SUN-351 Are We Underestimating The Role Of Systemic Chemotherapy In The Treatment Of Localized And Advanced Adrenocortical Carcinoma? - Ferreira, Amanda (J Endocr Soc, 2019)
Background: Adrenocortical carcinoma (ACC) is a rare and, in the vast majority of cases, aggressive neoplasia. Even in cases of localized disease at the diagnosis in which complete surgical resection of the tumor is performed, rates of local and distant recurrence are very high. Aim: To retrospectively analyze the management and outcomes of cases that presented localized disease (Group 1) and metastatic disease at diagnosis (Group 2) followed in a single Institution. Results: Group 1 was formed by 23 cases and group 2 by 7 cases. In group 1, adjuvant treatment was initiated in 17 patients: 9 received adjuvant radiotherapy (ARDT) associated with mitotane and 8 patients received mitotane alone; six patients have been followed expectantly. Recurrence of the disease was observed in 70% of the cases (n=16). All had distant metastasis and 6 out of 16 also had local recurrence. Most frequent sites of metastasis were lung, liver and peritoneum, including a rare case of heart metastasis. All patients with recurrence received systemic chemotherapy. No patient who was followed without adjuvant treatment has recurred so far. The median recurrence free survival (RFS) and overall survival (OS) were 13 and 30 months, respectively. In group 2, 5 patients had only one site of metastasis at diagnosis (all of them presented lung metastases) and the remaining cases had two (lung and liver) or three sites (lung, liver and bone). In only one case neoadjuvant chemotherapy was the treatment of choice. In the remaining patients, primary tumor was resected and systemic chemotherapy and mitotane started after surgery. The number of chemotherapy regimens ranged from one to four. Median progression free survival (PFS) was 2 months (range, 0.9 to 11 months) and OS was 11 months (range, 0.9 to 30 months). Patients who had more than one metastatic site at diagnosis had a lower survival rate and the patient who underwent neoadjuvant chemotherapy presented the longest PFS (11 months). Conclusions: Group 1 cases analysis reinforces the high rate of disease recurrence in patients with localized disease despite adjuvant treatment with ARDT and mitotane. These findings support the need for multicenter clinical trials to investigate the benefit of systemic chemotherapy in an adjuvant setting in patients at high risk of recurrence. Regarding the metastatic patients at diagnosis, we emphasize the importance of a greater experience with neoadjuvant chemotherapy.